Perlunya Penambahan AWOS DISPLAY pada Approach Control Surveillance untuk Mengurangi Load Of Coordination Air Traffic Controller di Perum LPPNPI Cabang Tanjungpinang - Martha Saulina; Bayu Ferdianto (Politeknik Penerbangan Indonesia Curug, 2023)
Raja Haji Fisabilillah International Airport is an international airport located in Tanjungpinang City. The Air Traffic Control Unit at Raja Haji Fisabilillah is divided into two units, namely the Aerodrome Control Tower and Approach Control Surveillance. This study aims to reduce the Load Of Coordination ATC. The unavailability of the AWOS Display facility in the Approach Control Surveillance room resulted in a lot of coordination by the ATC on duty when bad weather occurred, thus making the pilots wait for meteorological information updates. In fact, the ATC that manages the Approach Control Surveillance often coordinates in advance with the ATC that manages the Aerodrome Control Tower to ask about the weather at that time even though they have already received weather information from the Meteorology Unit. Various obstacles that often arise in the world of aviation are inseparable from the lack of existing facilities, including facilities in the air traffic staff workspace where these facilities are used to carry out air traffic services, as well as facilities on the runway. air traffic control area that functions to ensure the safety and smooth operation of flights.